2020
DOI: 10.1039/d0gc02689a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the coordination number of Fe single atoms for the efficient reduction of CO2

Abstract: CO2 electroreduction into valuable products holds great promise for energy supply and environmental remediation but remains a challenge due to the lack of high-performance electrocatalysts. Herein, we developed an efficient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…Moreover, as shown in Figure 8g , the axial pyrrolic‐N ligand on the FeN 5 sites could deplete the electron density of Fe 3d orbitals and reduce the Fe‐CO p back‐donation as compared to FeN 4 , hence leading to fast desorption of CO. Furthermore, Fe‐N 6 catalyst was compared to Fe‐N 5 by Chen and co‐workers, [ 85 ] in which, Fe‐N 5 catalyst reached a lower overpotential (50 mV) and exhibited a higher CO FE (up to 99%), j CO and CO TOF than the Fe‐N 6 catalyst in a broad potential range of −0.35–−1.05 V versus RHE. The superior performance was attributed to the Fe‐N 5 site, which facilitated the *COOH formation (Figure 8h,i ).…”
Section: Regulation Of Active Center and Local Atomic Environment In M‐n‐c Catalystsmentioning
confidence: 99%
“…Moreover, as shown in Figure 8g , the axial pyrrolic‐N ligand on the FeN 5 sites could deplete the electron density of Fe 3d orbitals and reduce the Fe‐CO p back‐donation as compared to FeN 4 , hence leading to fast desorption of CO. Furthermore, Fe‐N 6 catalyst was compared to Fe‐N 5 by Chen and co‐workers, [ 85 ] in which, Fe‐N 5 catalyst reached a lower overpotential (50 mV) and exhibited a higher CO FE (up to 99%), j CO and CO TOF than the Fe‐N 6 catalyst in a broad potential range of −0.35–−1.05 V versus RHE. The superior performance was attributed to the Fe‐N 5 site, which facilitated the *COOH formation (Figure 8h,i ).…”
Section: Regulation Of Active Center and Local Atomic Environment In M‐n‐c Catalystsmentioning
confidence: 99%
“…Currently, the active centers of the common M‐N‐C for CO 2 RR are the four‐coordinated structure of the M‐N 4 moiety, [39–42] and the M‐N 4 moiety exhibits a symmetric electronic distribution resulting from the symmetrical planar structure. Recently, the efficiency of CO 2 RR has been significantly improved over the M‐N 5 ‐C, [43–45] which resembled the axial ligand‐coordinated natural metal enzymes, indicating that the axial coordination environment plays a crucial role on the adsorption and activation of the CO 2 RR‐relevant species. Inspired by the structure of natural metal enzymes (heme of cytochrome P450 and azotase), we envision that designing the distinct axial coordination for SACs can significantly optimize the selectivity and activity of CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…The lower d‐band center of Co‐N 2 (−0.81 eV) than Co‐N 4 (−1.06 eV) results in the stronger CO 2 ·− binding 112 . Moreover, Geng and Zeng et al 113 compared Fe–N 5 and Fe–N 6 moieties for CO 2 ‐to‐CO reaction, and found the Fe–N 5 species has lower free energy to form *COOH, and the C on *COOH displays higher electron density on Fe–N 5 than on Fe–N 6 , ensuring the better performance of Fe–N 5 . Apart from the coordination number, the coordinated N ligands can also affect the ECR.…”
Section: Electrocatalysts Of Ecr Reactionmentioning
confidence: 98%